Polymeric nanocapsules prevent oxidation of core-loaded molecules: evidence based on the effects of docosahexaenoic acid and neuroprostane on breast cancer cells proliferation. Issue 1 (December 2015) - Roy, Jérôme; Oliveira, Liliam; Oger, Camille; Galano, Jean-Marie; Bultel-Poncé, Valerie; Richard, Sylvain; Guimaraes, Andrea; Vilela, José; Andrade, Margareth; Durand, Thierry; Besson, Pierre; Mosqueira, Vanessa; et al.
Abstract Background Nanocapsules, as a delivery system, are able to target drugs and other biologically sensitive molecules to specific cells or organs. This system has been intensively investigated as a way to protect bioactives drugs from inactivation upon interaction with the body and to ensure the release to the target. However, the mechanism of improved activity of the nanoencapsulated molecules is far from being understood at the cellular and subcellular levels. Epidemiological studies suggest that dietary polyunsaturated fatty acids (PUFA) can reduce the morbidity and mortality from breast cancer. This influence could be modulated by the oxidative status of the diet and it has been suggested that the anti-proliferative properties of docosahexaenoic acid (DHA) are enhanced by pro-oxidant agents. Methods The effect of encapsulation of PUFA on breast cancer cell proliferation in different oxidative medium was evaluated in vitro. We compared the proliferation of the human breast cancer cell line MDA-MB-231 and of the non-cancer human mammary epithelial cell line MCF-10A in different experimental conditions. Results DHA possessed anti-proliferative properties that were prevented by alpha-tocopherol (an antioxidant) and enhanced by the pro-oxidant hydrogen peroxide that confirms that DHA has to be oxidized to exert its anti-proliferative properties. We also evaluated the anti-proliferative effects of the 4(RS )-4-F4t -neuroprostane, a bioactive, non-enzymatic oxygenated metabolite of DHA known to play a major role in the prevention of cardiovascular diseases. DHA-loaded nanocapsules was less potent than non-encapsulated DHA while co-encapsulation of DHA with H2 O2 maintained the inhibition of proliferation. The nanocapsules slightly improves the anti-proliferative effect in the case of 4(RS )-4-F4t -neuroprostane that is more hydrophilic than DHA. Conclusion Overall, our findings suggest that the sensitivity of tumor cell lines to DHA involves oxidized metabolites. They also indicate that neuroprostane is a metabolite participating in the growth reducing effect of DHA, but it is not the sole. These results also suggest that NC seek to enhance the stability against degradation, enhance cellular availability, and control the release of bioactive fatty acids following their lipophilicities.